The role of food value on host use by the herbivorous amphipod Sunamphitoe pelagica - Andrade, Aynara R. [UNESP]; Paula, Caio A. [UNESP]; Leite, Fosca P.P.; Costa, Tânia M. [UNESP]; Machado, Glauco B.O. [UNESP] (Elsevier, 2024)
Mesograzers often use macrophytes as both food and habitat and may have strong effects on primary producers. In this context, understanding the factors mediating their interaction with macrophytes, such as host food value, is an important step to predict the impacts of these herbivores on aquatic ecosystems. The amphipod Sunamphitoe pelagica is a mesograzer with distribution restricted to a few brown macroalgal hosts, however it is unclear if food value drives host use by this mesograzer. Herein, we investigated the distribution of S. pelagica and the food value of its hosts. For that, the abundance of S. pelagica on the macroalgae Sargassum filipendula, Padina gymnospora, and Dichotomaria marginata was evaluated seasonally in a subtidal rocky shore at Fortaleza Beach (23°32′S, 45°10′W), state of São Paulo, Brazil. Furthermore, we conducted laboratory experiments to test feeding preference and rate, as well as the performance (e.g. survival, growth, and reproductive potential) of S. pelagica using the same macroalgal hosts used in the field abundance investigation. Overall, the mesograzer was more abundant on the brown macroalgae Sargassum and Padina than on the red macroalga Dichotomaria. In both feeding preference and rate experiments, S. pelagica consumed more Sargassum and Padina than Dichotomaria. Moreover, the consumption of Padina and Sargassum resulted in high performance of this mesograzer, while juveniles raised on Dichotomaria had a low survival, perishing within few days of experiment. These results suggest the host use by S. pelagica is strongly driven by the food value of macroalgal hosts and are in accordance with the narrow host breadth of this mesograzer. Therefore, considering the vulnerability of large macroalgae to climate change and habitat alterations, the restricted host use by S. pelagica to few brown macroalgae may increase its risk of local extinction.
Keywords: Feeding choice; Herbivore performance; Herbivore-plant interaction; Macroalgae; Mesograzer